A study of RC bridge columns under contact explosion. (November 2017) - Yuan, Sujing; Hao, Hong; Zong, Zhouhong; Li, Jun
Highlights: RC bridge columns are tested under contact explosions. Concrete spallation of the proximal and side faces of the two columns were observed. Numerical models for the two columns are developed in LS-DYNA. Comparisons between experimental and numerical results are carried out. Damage mechanisms of the columns under contact explosions are investigated. Abstract: This paper presents a study on reinforced concrete (RC) bridge columns under contact detonation. Two 1/3 scale RC bridge columns with circular and square cross-sections are studied both experimentally and numerically. Field tests were performed on two types of columns under 1 kg TNT contact explosion, and acceleration data at different heights of the columns were collected by accelerometers. Investigation of the damage evolution and structural local response is conducted by high-fidelity physics-based numerical models that are developed in the commercial program LS-DYNA through the Arbitrary Lagrangian–Eulerian (ALE) algorithm. The results from the numerical simulation are compared with the experimental results. Field blast tests showed that for both columns the cover concrete on the proximal and side surfaces close to the explosive charge suffered serious damage, while the cover concrete on the distal face remained almost intact. Due to the column geometry, the contact explosion caused larger blast loads on the square column leading to more severe damage. The damage mechanism of the two columns is discussed based on numerical simulations. The results from the numerical model match well with those from the tests except for the back-surface damage in both cases. Field data obtained from accelerometers also show reasonable agreement with results from the numerical modelling and confirm the localized structural response of the columns under contact blast loads. It is shown that the numerical models established in this study provide reliable predictions for the structural response of bridge columns under contact explosion.